Assessment of motion and model bias on the detection of dopamine response to behavioral challenge. Issue 7 (July 2022) - Levine, Michael A; Mandeville, Joseph B; Calabro, Finnegan; Izquierdo-Garcia, David; Chonde, Daniel B; Chen, Kevin T; Hong, Inki; Price, Julie C; Luna, Beatriz; Catana, Ciprian
Compartmental modeling analysis of 11 C-raclopride (RAC) PET data can be used to measure the dopaminergic response to intra-scan behavioral tasks. Bias in estimates of binding potential (BPND ) and its dynamic changes (ΔBPND ) can arise both when head motion is present and when the compartmental model used for parameter estimation deviates from the underlying biology. The purpose of this study was to characterize the effects of motion and model bias within the context of a behavioral task challenge, examining the impacts of different mitigation strategies. Seventy healthy adults were administered bolus plus constant infusion RAC during a simultaneous PET/magnetic resonance (MR) scan with a reward task experiment. BPND and ΔBPND were estimated using an extension of the Multilinear Reference Tissue Model (E-MRTM2) and a new method (DE-MRTM2) was proposed to selectively discount the contribution of the initial uptake period. Motion was effectively corrected with a standard frame-based approach, which performed equivalently to a more complex reconstruction-based approach. DE-MRTM2 produced estimates of ΔBPND in putamen and nucleus accumbens that were significantly different from those estimated from E-MRTM2, while also decoupling ΔBPND values from first-pass k2 ′ estimation and removing skew in the spatial bias distribution of parametric ΔBPND estimates within the striatum.